Urban lignocellulosic biomass can significantly contribute to energy production in municipal wastewater treatment plants – A GIS-based approach for a metropolitan area. (October 2015) - Kosse, Pascal; Lübken, Manfred; Wichern, Marc
Abstract: The common fermentation of biogenic wastes and sewage sludge in digesters of municipal wastewater treatment plants is a technically feasible and economically viable approach. As the number of rural biogas production sites is steadily increasing, the question has been raised which biomass feedstocks are left available in sufficient quantities to be used for energy generation at wastewater treatment plant level. The contribution of lignocellulosic biomass collected from urban areas is generally neglected within this context. In the present study, 24 urban substrates have been analyzed for their theoretical methane potential, while 13 of them were tested in batch assays for the determination of their practical achievable methane yield. The theoretical evaluation of the methane potential yielded values ranging between 0.393 and 0.576 Nm 3 kgVS −1 . The methane yields obtained by batch assays showed significantly lower yields, which depends on the individual composition of the substrates in terms of lignin, hemicellulose and cellulose. A GIS spatial analysis for the Rhine-Ruhr metropolitan area was performed to evaluate the feasible capacity of urban biomass as co-fermentation feedstock in digesters of municipal wastewater treatment plants. The analysis revealed that green urban areas provide a significant quantity of biomass of 377 tFM  d −1 that could cover 67% of the annual energy demand of twelve typical wastewater treatment plants located in the metropolis. Highlights: Determination of chemical compositions and theoretical methane yields of 24 urban lignocellulosic substrates. Determination of practical achievable biogas and methane yields of 13 urban lignocellulosic substrates using BMP tests. Quantification of available urban biomass for the Rhine-Ruhr metropolitan area by means of a GIS-based spatial analysis. Evaluation of the potential of urban biomass as feedstock for co-fermentation in digesters of wastewater treatment plants.